Surgery in oesophago-gastric cancer with metastatic disease: Treatment, prognosis and preoperative patient selection. Issue 10 (October 2015) - Schmidt, T.; Alldinger, I.; Blank, S.; Klose, J.; Springfeld, C.; Dreikhausen, L.; Weichert, W.; Grenacher, L.; Bruckner, T.; Lordick, F.; Ulrich, A.; Büchler, M.W.; et al.
Abstract Background The role of surgical resection in metastatic oesophago-gastric adenocarcinomas (EGA) is not defined and regularly discussed in interdisciplinary tumour boards. Primary objective of this retrospective study was the outcome of patients after surgery. We additionally evaluated our preoperative prognostic score (PPS) based on tumour grading, clinical response to chemotherapy and presumed R-status. Methods 123 of 811 EGA patients were evaluated as cM1, either confirmed intraoperatively or by imaging. Response evaluation after chemotherapy was performed by endoscopy, CT-scan and histopathologically. The prospectively documented patient and outcome data were analysed retrospectively. Results 70 patients with adenocarcinoma of the oesophago-gastric junction and 53 patients with gastric cancer were included. The majority had one M1 site (n = 102). 72 received preoperative chemotherapy (CTx) and 51 underwent primary resection. 11 were explored without resection. 49/112 (40%) had multivisceral resections and 63/112 (56%) were completely resected (R0). 26/72 (36%) were clinical responders and 30 patients had a favourable PPS. Median survival was 20.0 months. Survival was significantly prolonged by resection, especially complete resection, and by preoperative CTx (all p = 0.001). Multivisceral resection, type or number of metastases, or primary tumour localization had no impact on survival. In patients undergoing preoperative CTx, clinical response and the PPS influenced survival significantly. In R0 resected patients, preoperative CTx, clinical response and the PPS remained prognostic. Conclusion Primary resection without preoperative CTx is not appropriate for metastatic EGA. Subgroups of patients with a favourable PPS with response to CTx may be good candidates for surgical resection in metastatic oesophago-gastric cancer.